-induced thrombocytopenia: a retrospective study of 16 patients - Songsong Xie; Yan Zhou; Rongjiong Zheng; Weize Zuo; Xiaobo Lu; Yuanzhi Wang; Yuexin Zhang (Journal of International Medical Research, 2019)
Objective We aimed to describe the clinical characteristics and treatment outcomes of 16 patients with Brucella -induced thrombocytopenia. Methods We assessed 16 patients with Brucella -induced thrombocytopenia between 2012 and 2016 in The First Affiliated Hospital of Xinjiang Medical University. The diagnosis of Brucella -induced thrombocytopenia was ≤100,000 platelets/mm 3 . Results All patients were men. The most common symptoms of patients were fever (100%), sweating (81.2%), fatigue (75%), and joint pain (25%). The most common signs of physical examinations were an enlarged liver (75%) and enlarged spleen (50%). The lowest thrombocyte count was 2000/mm³ and the highest count was 72,000/mm³. An agglutination test antibody was positive (≥1:160) in 12 (75%) patients with the highest antibody titer of 1:800. Brucella melitensis was isolated from blood cultures in nine (56.3%) patients. All patients were administered antimicrobial agents. The patients’ platelet counts were normal at a follow-up of 12 months. Conclusion Classical brucellosis therapy is adequate for patients with a platelet count > 20,000/mm 3 . The five-drug regimen of doxycycline + rifampin + platelet transfusions +  corticosteroids + intravenous immunoglobulin is recommended for patients when the platelet count is < 10,000/mm 3 . These findings have important implications for improving treatment outcome in patients with Brucella -induced thrombocytopenia.